If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2x = 15 + -3x Solving 9 + 2x = 15 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 9 + 2x + 3x = 15 + -3x + 3x Combine like terms: 2x + 3x = 5x 9 + 5x = 15 + -3x + 3x Combine like terms: -3x + 3x = 0 9 + 5x = 15 + 0 9 + 5x = 15 Add '-9' to each side of the equation. 9 + -9 + 5x = 15 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 15 + -9 5x = 15 + -9 Combine like terms: 15 + -9 = 6 5x = 6 Divide each side by '5'. x = 1.2 Simplifying x = 1.2
| 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 | | 7(9+-2x)=9(7x-2) | | 16x^2-11x+26=0 | | 9c-36= | | (x+y)dx+(x-y)dy=0 | | 7(5-4)+3x=4(x+2) | | -13-7x=9x-11 | | 12x+7=-4x+9 | | -15=-5y | | 8x+4/2=4x-2/3 | | 15/3-7x=9+5x | | 27-6d=7+4 | | 57/9+48/9 | | 15-10=6x-(x+2)+(-x+3) | | (4x-1)-(x-3)= |